PENINGKATAN HASIL BELAJAR BIOLOGI SISWA KELAS II SMUN I SELAT PANJANG MELALUI PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) - Evi Suryawati; Mariani Natalina; lili Arliza; SaImiah ' (Biogenesis, 2005)
Have done the classroom action research was to know the increase of result  learn biology with to approach of STAD Cooperative learning to student class II SMUN  1 Selat Panjang on February – April 2004.  Samples were collected students class II.1  to amount 42 people.  Various parameters such as: Student reserve capacity, produce student learn, student development value, teams appreciation value and students activity. The result of student learn at Cycle I with concept Food and Digestion System at meeting I (81,62), meeting II (79,02), meeting III  (74,22) and meeting IV (82.43). At Cycle II with concept Excretory System of average value at meeting I (83,59), meeting II  (84,86) and meeting 111 (87,29). For student development that contribute for teams appreciation value at Cycle I, 8 teams to get super appreciations and  1 team to get enormous appreciation. Whereas at Cycle II, from 9 teams, all teams to get super appreciations. The Student activity in cycle I equal to 77.19 (very well category), cycle II  equal  to 84.85  (in  very  well  category).  Based  on  the research result,  that  approach of STAD Cooperative Learning can to increase the result of student learning.   Key words : Biology, Cooperative learning